Radical scavenging capacity, antibacterial activity, and quantum chemical aspects of the spectrophotometrically investigated iridium (III) complex with benzopyran derivative - Mohmad, Masrat; Agnihotri, Nivedita; Kumar, Vikas; Azam, Mohammad; Wabaidur, Saikh Mohammad; Kamal, Raj; Kumar, Rakesh; Alam, Mahboob; Kaviani, Sadegh (Frontiers in Pharmacology, 2022)
A comprehensive aqueous phase spectrophotometric study concerning the trace level determination of iridium (III) by its reaction with benzopyran-derived chromogenic reagent, 6-chloro-3-hydroxy-7-methyl-2-(2′-thienyl)-4-oxo-4H-1-benzopyran (CHMTB), is performed. The complexing reagent instantly forms a yellow complex with Ir (III) at pH 4.63, where metal is bound to the ligand in a ratio of 1:2 as deduced by Job’s continuous variations, mole ratio, and equilibrium shift methods. The complex absorbs maximally at 413–420 nm retaining its stability for up to 4 days. An optimum set of conditions have been set with respect to the parameters governing the formation of the complex. Under the set optimal conditions, the Ir (III)-CHMTB complex coheres to Beer’s law between 0.0 and 1.5 µg Ir (III) mL−1. The attenuation coefficient and Sandell’s sensitivity are, respectively, 1.18×105 L mol−1 cm−1 and 0.00162 μg cm−2 at 415 nm. The correlation coefficient (r) and standard deviation (SD) were 0.9999 and ± 0.001095, respectively, whereas the detection limit as analyzed was 0.007437 μg ml−1. The interference with respect to analytically important cations and complexing agents has been studied thoroughly. It is found that the majority of the ions/agents do not intervene with the formation of the complex, thus adding to the versatility of the method. The results obtained from the aforesaid studies indicate a simple, fast, convenient, sensitive, and versatile method for microgram analysis of iridium (III) using CHMTB as a binding ligand. Furthermore, the studied complex is subjected to the evaluation of antibacterial and antioxidant capacity by employing the Agar Diffusion assay and DPPH. radical scavenging method, respectively. The results obtained from the mentioned assays reveal that the investigated complex possesses significant potency as an antibacterial and antioxidant agent. Finally, the computational approach through DFT of the formed complex confirmed the associated electronic properties of the studied complex.